Coexisting Rathke Cleft Cyst and Pituitary Adenoma Presenting with Pituitary Apoplexy: Report of Two Cases - Gessler, Florian (Thieme Medical Publishers, 2011)
The authors report two cases of coexisting Rathke cleft cyst (RCC) and pituitary macroadenoma. Both patients presented at the university hospital with pituitary apoplexy symptoms of sudden-onset headache while undergoing treatment with Coumadin (warfarin). Magnetic resonance imaging was consistent with a pituitary adenoma in one case and RCC in the other. Intraoperative findings and pathological work-up identified RCC along with adenomatous tissue displaying hemorrhagic pituitary adenoma in one and hemorrhagic RCC in the other. Clinical symptoms of pituitary apoplexy were present in both cases, making pituitary and RCC apoplexy clinically indistinguishable. RCC and concomitant pituitary adenoma are a rare intraoperative finding that must be considered as a differential diagnosis in patients with symptoms of pituitary adenoma apoplexy.